Proteins Involved in Synaptic Plasticity Are Downregulated in the Cerebrospinal Fluid of Infants With Clinical Sepsis Complicated by Neuroinflammation - Jiang, Ping-Ping; Peng, Shan-Shan; Pankratova, Stanislava; Luo, Ping; Zhou, Ping; Chen, You (Frontiers in Cellular Neuroscience, 2022)
Preterm infants are prone to clinical sepsis and related inflammation of different organs. Neuroinflammation has been associated with long-term adverse neuronal (neuropsychiatric/neurodegenerative) outcomes, including ADHD or even Alzheimer’s disease. Despite a vast number of findings on sepsis-induced inflammatory responses in the central nervous system (CNS), how neuroinflammation affects brain development remains largely elusive. In this study, neonates with clinical sepsis and screened for meningitis were included and classified by the neuroinflammation status based on CSF parameters (NeuINF vs. CON). CSF samples collected from clinical screening were subjected to proteomics analysis. Proteins with differential abundance were subjected to enrichment analysis to reveal affected biological pathways. NeuINF and CON infants had similar demographic data and hematological and biochemical parameters in blood and CSF. The CSF proteomes were essentially different between the two groups. All 65 proteins with differential abundance showed lower abundance in the NeuINF group and functionally covered pivotal developmental processes, including axonal and synaptic function and extracellular homeostasis. CSF proteins, PTPRZ1 and IGFBP4, were correlated with CRP and ratios of immature/total neutrophils in blood. In general, a substantial change in the CSF protein profile was found under neuroinflammation, and these changes are related to systemic conditions. The results suggest that changes in CSF proteins may be involved in sepsis-affected neurodevelopment, such as disturbances in circuit formation, which has the potential to predispose neonates to long-term adverse outcomes.